1966
DOI: 10.1042/bj0990053
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological properties of an extracellular lipopolysaccharide from Escherichia coli grown under lysine-limiting conditions

Abstract: Lipopolysaccharide was prepared from the extracellular lipoglycopeptide produced by the lysine-requiring mutant Escherichia coli A.T.C.C. 12408 grown under lysine-limiting conditions. The lipid moiety, containing glucosamine phosphate and four fatty acids (lauric acid, myristic acid, beta-hydroxymyristic acid and palmitic acid) corresponded in composition to lipid A of known bacterial lipopolysaccharides. The components of the polysaccharide moiety were d-glucose, d-galactose, l-glycero-d-manno-heptose, 3-deox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

1967
1967
1971
1971

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 35 publications
(16 reference statements)
3
33
0
Order By: Relevance
“…The origin of these substances in culture fluids is uncertain, but it seems unlikely that they result from leaching or lysis of the bacteria during growth. Taylor et al (1966) showed that their lipopolysaccharide was excreted by a. rough lysine-dependent mutant when lysine was deficient in the medium, whereas the E. coli 078 K80 (used in the present work) was a smooth ovine enteropathogen without any unusual requirements. As Taylor et al (1966) found, the endotoxin in the culture fluid appeared to be derived by excretion from the bacteria rather than b y lysis or leaching.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The origin of these substances in culture fluids is uncertain, but it seems unlikely that they result from leaching or lysis of the bacteria during growth. Taylor et al (1966) showed that their lipopolysaccharide was excreted by a. rough lysine-dependent mutant when lysine was deficient in the medium, whereas the E. coli 078 K80 (used in the present work) was a smooth ovine enteropathogen without any unusual requirements. As Taylor et al (1966) found, the endotoxin in the culture fluid appeared to be derived by excretion from the bacteria rather than b y lysis or leaching.…”
Section: Discussionmentioning
confidence: 70%
“…Taylor et al (1966) showed that their lipopolysaccharide was excreted by a. rough lysine-dependent mutant when lysine was deficient in the medium, whereas the E. coli 078 K80 (used in the present work) was a smooth ovine enteropathogen without any unusual requirements. As Taylor et al (1966) found, the endotoxin in the culture fluid appeared to be derived by excretion from the bacteria rather than b y lysis or leaching. The non-toxic fraction probably arose similarly, although its rdation to endotoxin is not yet established (Marsh & Crutchley, 1967).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Shear & Turner, 1943) have isolated tumour-necrotizing substances (endotoxins) from supernatant fluids of cultures of Gram-negative bacteria, most other workers have preferred to extract endotoxins from the bacteria themselves. An exception has been Work and her collaborators (Bishop & Work, 1965, Taylor, Knox & Work, 1966' who found endotoxic lipopolysaccharides in culture supernatant fluids of lysinerequiring mutants of Escherichia coli grown under lysine-limited conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Shear & Turner, 1943) have isolated tumour-necrotizing substances (endotoxins) from supernatant fluids of cultures of Gram-negative bacteria, most other workers have preferred to extract endotoxins from the bacteria themselves. An exception has been Work and her collaborators (Bishop & Work, 1965, Taylor, Knox & Work, 1966' who found endotoxic lipopolysaccharides in culture supernatant fluids of lysinerequiring mutants of Escherichia coli grown under lysine-limited conditions.The release of large quantities of free endotoxin into the culture supernatant fluids of Gram-negative bacteria, under favourable growth conditions, has recently been described (Crutchley, Marsh & Cameron, 1967a). The present paper will deal with the fractionation of supernatant fluids of cultures of Escherichia coli serotype 078K80 and the subsequent physical and chemical characterization of the fractions ; the accompanying paper (Crutchley et al 1967 b) will discuss the biological properties of these fractions.…”
mentioning
confidence: 99%